1993
DOI: 10.1016/0014-5793(93)81010-w
|View full text |Cite
|
Sign up to set email alerts
|

TRP‐1 expression correlates with eumelanogenesis in human pigment cells in culture

Abstract: We have investigated the relationship in human cultured normal and malignant melanocytes between the accumulation of mRNAs encoding tyrosinase and tyrosinase-related protein-l (TRP-I), the activity of tyrosinase and the presence of melanin. Tyrosinase mRNA correlates with tyrosinase activity and with the presence of pheomelanin, eumelanin or both melanin types. In contrast TRP-1 mRNA is only detectable in cells containing eumelanin, which suggests a role for TRP-1 in the eumelanin synthesis pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0
1

Year Published

1994
1994
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(57 citation statements)
references
References 19 publications
2
54
0
1
Order By: Relevance
“…Moreover, in human cell lines, expression of TRP-1 was only detectable in cells containing eumelanin [43]. The DHI-CA oxidase activity described for TRP-1 implicates this enzyme in the synthesis of eumelanin.…”
Section: Trps and Melanogenesismentioning
confidence: 93%
“…Moreover, in human cell lines, expression of TRP-1 was only detectable in cells containing eumelanin [43]. The DHI-CA oxidase activity described for TRP-1 implicates this enzyme in the synthesis of eumelanin.…”
Section: Trps and Melanogenesismentioning
confidence: 93%
“…In addition to tyrosinase, several other structurally related proteins are encoded by the tyrosinase gene family, notably tyrosinase-related protein 1 (TRP-1) (19,20) and tyrosinase-related protein 2 (TRP-2) (21-23). These two molecules are also involved in the melanin synthesis pathway, both of them contributing more to the synthesis of eumelanin than to pheomelanin (24)(25)(26). TRP-1 and TRP-2 share moderate sequence similarities with tyrosinase, the amino acid homology with the tyrosinase being 43% and 40%, respectively (22,25).…”
Section: Discussionmentioning
confidence: 99%
“…TRP-1 and TRP-2 reside within the melanosomes and, like tyrosinase, span the melanosomal membrane [15]. It has been suggested that TRP-1 increases the ratio of eumelanin to pheomelanin [16,17]. In addition, they have been demonstrated to increase tyrosinase stability [18,19].…”
Section: Melanogenesismentioning
confidence: 99%